Two-phase flow in the localized boiling field adjacent to a heated wall - Bonetto, Fabián José; Clausse, Alejandro; Converti, José (Comisión Nacional de Energía Atómica; Argentina)
Fil: Bonetto, Fabián José Comisión Nacional de Energía Atómica; Argentina